Going straight to the source: A pilot study of bereaved parent‐facilitated communication training for pediatric subspecialty fellows. Issue 1 (8th September 2016) - Snaman, Jennifer M.; Kaye, Erica C.; Cunningham, Melody J.; Sykes, April; Levine, Deena R.; Mahoney, Daniel; Baker, Justin N.
Abstract: Background: Medical trainees consistently report suboptimal instruction and poor self‐confidence in communication skills. Despite this deficit, few established training programs provide comprehensive, pediatric‐specific communication education, particularly in the provision of "bad news." To our knowledge, no programs currently use bereaved parent educators to facilitate communication training for pediatric subspecialty trainees. Procedure: The authors designed and implemented a pilot communication training seminar in which bereaved parent educators and faculty facilitators led small groups in interactive, role‐play scenarios. Surveys incorporating a retrospective preprogram assessment item to account for response‐shift bias were used to assess short‐ and long‐term changes in trainee comfort with delivering "bad news." Results: Fifteen pediatric fellowship trainees participated in the communication seminar; complete data were available for 12 participants. After accounting for response‐shift bias, participants reported significant improvement in overall preparedness, breaking bad news to a patient and family, and including the adolescent or young adult patient in conversations. Additionally, participants reported a significant improvement in their ability to address a patient and family's need for information, emotional suffering at the end of life (EOL), if and when a patient should be included in the conversation, and EOL care decisions. The participant's self‐perceived improvement in comfort and preparedness persisted over time. Conclusions: Communication training for pediatric subspecialty trainees using bereaved parent educators is feasible and effective. Both medical trainee and bereaved parent participants benefited from involvement in this pilot study. Further iterations of this training will be modified to assess objective measures of improvement in trainees' communication skills.